Knowledge and attitude of women towards maternity waiting homes and associated factors among women who gave birth in the last twelve months in Dega Damot district, northwest Ethiopia - Anteneh, Tazeb Alemu; Solomon, Abayneh Aklilu; Tamiru, Animut Tagele; Tibebu, Nebiyu Solomon; Abegaz, Marta Yimam; Temesgan, Wubedle Zelalem; Kebede, Azmeraw Ambachew; Aklil, Mastewal Belayneh; Mesele, Tiruye Tilahun; Tiruye, Tiringo Molla (Frontiers in Global Women's Health, 2023)
Background: Maternal waiting homes have been identified as one strategy to reduce maternal and perinatal mortality by bringing women living in hard-to-reach areas closer to a health facility that provides emergency obstetric care. Lack of awareness and poor women attitudes are leading factors for the underutilization of maternal waiting homes. Even if utilization of maternal waiting homes is repeatedly assessed, there is a scarcity of evidence in Ethiopia regarding women’s knowledge and attitude towards maternal waiting homes. Objective: This study aimed to assess women’s knowledge and attitude towards maternity waiting homes and associated factors among women who gave birth in the last twelve months in Dega Damot district, northwest Ethiopia. Methods: A community-based cross-sectional study was conducted from January 1st to February 30th, 2021. A total of 872 participants were selected by using a stratified cluster sampling technique. Data were collected by face-to-face interviews using a structured, pretested, and interviewer-administered questionnaire. Data were entered into EPI data version 4.6 and analysis was done through SPSS version 25. The multivariable logistic regression model was fitted and the level of significance was declared at a p-value of ≤ 0.05. Result: Women’s knowledge and positive attitude towards maternal waiting homes were 67.3% (95% CI: 64-70) and 73% (95% CI: 70-76), respectively. Had antenatal care visits, short distances to reach the nearby health facility, had a history of maternal waiting homes utilization, always involved in health care decisions, and sometimes involved in health care decisions were significantly associated with women’s knowledge regarding maternal waiting homes. Moreover, secondary and above educational level of women, short distance to reach the nearby health facility and had antenatal care visit were significantly associated with women’s attitude towards maternity waiting homes. Conclusion: About two-thirds of women had adequate knowledge and nearly three-fourths of women had a positive attitude toward maternity waiting homes. It is better to improve the accessibility and utilization of maternal health services Furthermore, it is better to promote women’s decision-making power and create motivation to have better academic achievement of women.